2018
DOI: 10.1063/1.5018719
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation kinetics of excited ions: PEPICO measurements of Os3(CO)12 — The 7-35 eV single ionization binding energy region

Abstract: In this article, we study the photoinduced dissociation pathways of a metallocarbonyl, Os(CO), in particular the consecutive loss of CO groups. To do so, we performed photoelectron-photoion coincidence (PEPICO) measurements in the single ionization binding energy region from 7 to 35 eV using 45-eV photons. Zero-energy ion appearance energies for the dissociation steps were extracted by modeling the PEPICO data using the statistical adiabatic channel model. Upon ionization to the excited ionic states above 13 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A potential strength, however, may be photon energy dependent fragmentation of precursor molecules, which has potential to further enhance the in-situ purity of the resulting FXBID deposits. It has been shown that X-ray induced fragmentation of certain relevant precursor molecules exhibits photon energy dependency not only in terms of fragmentation rates, but also fragmentation chemistry, i.e., changing relative intensities of various fragments [103,118,119]. Such effects could be exploited to select photon energies for FXBID that result in a high ratio of low mass fragments (in ideal cases only the metal center itself) versus high mass fragments leading to implantation of a large amount of alien atoms from the ligands into the resulting deposits.…”
Section: Perspectives Or: What Fxbid Might Be Good Formentioning
confidence: 99%
“…A potential strength, however, may be photon energy dependent fragmentation of precursor molecules, which has potential to further enhance the in-situ purity of the resulting FXBID deposits. It has been shown that X-ray induced fragmentation of certain relevant precursor molecules exhibits photon energy dependency not only in terms of fragmentation rates, but also fragmentation chemistry, i.e., changing relative intensities of various fragments [103,118,119]. Such effects could be exploited to select photon energies for FXBID that result in a high ratio of low mass fragments (in ideal cases only the metal center itself) versus high mass fragments leading to implantation of a large amount of alien atoms from the ligands into the resulting deposits.…”
Section: Perspectives Or: What Fxbid Might Be Good Formentioning
confidence: 99%